Chlorophyll a concentration of phytoplankton during cruises of the 40-44th Japanese Antarctic Research Expeditions in 1998-2003 - Hirawake, Toru; Fukuchi, Mitsuo (National Institute of Polar Research, 2004)
P(論文) departmental bulletin paper